The crazy case of missing Thunder - Abbott, Tony, 1952- (Goofballs, 2012)
Long-time friends and fellow sleuths Jeff Bunter, Brian Rooney, Mara Lubin, and Kelly Smitts, collectively known as the Goofballs, investigate the disappearance of Thunder the pony in their town of Badger Point.